The impact of agency cost on firm performance - Rohim, Sas Rifky Namulfaqi; Kurnianti, Destria; Nguyen, Tran Phuoc (Ifma Publishing, 2024)
This study aimed to determine the effect of agency cost on the performance of firms listed in the Kompas100 index on the Indonesia stock exchange for the 2016-2021 period. In determining the sample, this research applied the purposive sampling method. This study used a sample of 46 companies and managed a total of 248 observations. The findings indicated a negative and significant impact of agency cost on firm performance. Companies with a high agency cost tend to reduce the performance. Mitigating these adverse effects requires the implementation of robust internal controls, transparent reporting mechanisms, and effective corporate governance practices.